2019
DOI: 10.1155/2019/3898951
|View full text |Cite
|
Sign up to set email alerts
|

An Insider Threat Detection Approach Based on Mouse Dynamics and Deep Learning

Abstract: In the current intranet environment, information is becoming more readily accessed and replicated across a wide range of interconnected systems. Anyone using the intranet computer may access content that he does not have permission to access. For an insider attacker, it is relatively easy to steal a colleague’s password or use an unattended computer to launch an attack. A common one-time user authentication method may not work in this situation. In this paper, we propose a user authentication method based on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In the process of examining each article's reference list, materials that were frequently mentioned [18]- [24] were added to the final list even though they were not published recently. We also included three papers that attempted a novel approach [25]- [27], one article that investigated network-based detection in IoT environments [28], one article about insider threat detection in IoTs [29], and two articles of attack vectors considering IoTs [12], [16]. Deep-learning related ITD researches [30], [31] that show the excellent capabilities of detecting unseen behavior patterns have also been added.…”
Section: A Survey Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of examining each article's reference list, materials that were frequently mentioned [18]- [24] were added to the final list even though they were not published recently. We also included three papers that attempted a novel approach [25]- [27], one article that investigated network-based detection in IoT environments [28], one article about insider threat detection in IoTs [29], and two articles of attack vectors considering IoTs [12], [16]. Deep-learning related ITD researches [30], [31] that show the excellent capabilities of detecting unseen behavior patterns have also been added.…”
Section: A Survey Approachmentioning
confidence: 99%
“…The dataset fields include record timestamp, client timestamp, button, state, and x & y coordination. Hu et al [25] used this dataset in their study to show mouse biobehavioral features for ITD works.…”
Section: ) Balabit Mouse Dynamics Challenge Datasetmentioning
confidence: 99%
“…Ref. [ 3 ] proposed an insider threat detection method based on mouse biometrics and CNN networks with good results. Ref.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The attacker is a legitimate user, and possibly administrators of the system. Thus, the security facilities of the internal network cannot monitor or block such attacks [ 3 ]. Even if there are security logs, the attacker may delete them through other means.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the proposed method perform better that the existing log based anomaly detection techniques. In [322], Teng et al have proposed a CNN based user authentication technique which uses the dynamic behaviour of the mouse. The proposed model learns from the dynamic behaviour pictures and can authenticate user continuously for every 7 seconds.…”
Section: Deep Learning In Insider Threat Detectionmentioning
confidence: 99%